STUDENTS’ PERCEPTION ON THE USE OF ONLINE ASSESSMENT IN ENGLISH SUMMATIVE TEST AT ELEVENT GRADE OF SMAN 1 TANJUNG JABUNG BARAT - Mukhtar; Rozal, Edi; Mesalina, Juliana; Kurniati, Indah (JR-ELT (Journal of Research in English Language Teaching), 2020)
This research sought to determine how students at SMAN 1 Tanjung Jabung Barat perceive the use of online assessment in English summative exams. This research employed a qualitative research design in which data were collected through interviews and observations of IPA 11 students. Based on (Walgito, 2010) theory, the findings are presented in three categories: cognitive aspect, conative aspect, and affective aspect. According to the findings of the research, the majority of students have a favorable view of online assessment, particularly regarding its cognitive and conative aspects. The students viewed online assessment as an effective, interesting, and valuable method for conducting online examinations. The negative perception was associated with the affective aspect of the online assessment, which was perceived as somewhat intimidating. When the server is disrupted and the network is unstable, students become apprehensive.